HIDROLISIS SELULOSADARI BAHAN POD HUSK KAKAO MENGGUNAKAN ASAM KLORIDA - Rizal, Rizal; Hutomo, Gatot siswo; Rahim, Abdul (AGROTEKBIS, 2016)
The aims of this experiment were to obtain the best concentration of HCl and the optimum length of boiling time in producing liquid sugar from cacao pod husk. Analysis of data of extracted cellulose (Phase I) used completely randomized design (CRD), which consisted of 3 NaOH concentrations tested namely : 10%, 12% and 14%. Each treatment was replieated 4 times, and therefore there were 12 experimental units used. Analysis of variance showing significant or highly significant effects were subsequently analysed by HSD at 5% or 1%, respectively. Experimental design used in the hydrolysis of cellulose (Phase II) was randomized block design (RBD) with four levels of hydrochloric acid (HCl) tested, namely: K1 = 1%; K2 = 1.5%; K3 = 2% and K4 = 2.5%. Treatments were grouped based on the length of pod husk cellulose hydrolysis time in hydrochloric acid solution, namely R1 = 2 hours, R2 = 4 hours, R3 = 6 hours, R4 = 8 hours, R5 = 10 hours and R6 = 12 hours. Each treatment was replicated three times in each group, and therefore there were 72 experimental units observed. Analysis of variance showing significant or highly significant effects were subsequently analysed by HSD at 5% or 1%, respectively. The best NaOH concentration was obtained at 12% and the optimum length of boiling time was 8 hours.Key Words: Cacao pod husk, cellulose, Hydrochloric acid.